Digital-Based Basic Accounting Training for Accounting Students at SMK N 1 Pangkalpinang (Series: 2) - Yosefin; Muhammad Gifran (Asian Journal of Community Services, 2023)
Basic digital-based accounting skills, especially operating accounting computer applications, is a challenge for students majoring in accounting at SMK N 1 Pangkalpinang, given the ever-evolving application technology. The training we carry out can support students to improve their skills. Series training: 2 uses an accurate educational series application. This training consists of understanding and operating order financing with an accounting computer, analyzing return merchandise authorization (RMA), analyzing memorize transactions and recuring, operating file menus on an accounting computer, and operating reports with an accounting computer. Digital-based basic accounting training for students majoring in accounting at SMK N 1 Pangkalpinang (series: 2) has been successfully implemented, as seen from the ability of the trainees to operate accounting computer applications (accurate) and are able to make financial reports with accounting computers.